The The Communication of Scientific Knowledge about Family Planning in Costa Rica (1977-1985) - Jiménez Bolaños, José Daniel (2024)
Family planning programs began in Costa Rica officially at the end of the 1960s. Private organizations, in conjunction with the State, oversaw the development of strategies to offer these services. One of the main challenges was the communication of this knowledge to the popular classes. Being a voluntary program, it was necessary to communicate information to the couples about the different methods available, the advantages of planning and the implications of an adequate upbringing. The objective of this paper is to analyze the discursive display that allowed the communication of scientific knowledge about family planning in Costa Rica, using as a source the issues of the magazine Salud para todos, published by the Costa Rican Demographic Association between 1977 and 1985. From a theoretical perspective based on the dialogues between science, technology, and society (STS), the use of colloquial language was emphasized and, through images, dialogues and informative texts, basic information on family planning methods was provided. There were also discussions on gender roles and the effects they could have on planning.